Magnetically driven filament probe - Schmid, A.; Herrmann, A.; Rohde, V.; Maraschek, M.; Müller, H. W. (Review of scientific instruments, 2007)
A radially movable probe has been developed for studies of filamentary transport in ASDEX Upgrade during edge localized modes (ELMs) by means of Langmuir tips and magnetic pickup coils. The probe is permanently installed at the low field side in the ASDEX Upgrade vacuum vessel and is not subject to limitations in probe size, as, for example, probes on a shared manipulator are. The probe is moved by a magnetic drive, which allows for easy installation in the vessel, and has moderate machine requirements, as it will only require an electric feedthrough and an external power supply. The drive gives a linear motion with a radial range of 5 cm within 50 ms , where range and velocity can be largely scaled according to experimental requirements. The probe has been installed in the outer midplane of the ASDEX Upgrade vessel, where ELM filaments are expected to have their maximum amplitude. Filaments are coherent substructures within an ELM, carrying a fraction of the ELM released energy towards the wall. The new probe allows to measure the structure of these filaments, in particular, parameters such as filament rotation (by time delay measurements) and size (by peak width analysis). Activating the drive moves the probe from a safe position behind the limiter to a position in front of the limiters, i.e., exposes the Langmuir pins to the scrape-off layer plasma.